Barriers to Improving Energy Efficiency: Insights from Energy Services Companies in Jordan - Shahateet, Mohammed Issa; Khazali, Mohammed; Albaali, Ghani; Sweis, Nadia; Saidi, Abdul Ghafoor (International Journal of Energy Economics and Policy, 2021)
This work aims to examine the barriers to improving energy efficiency as encountered by Energy Services Companies (ESCOs) in Jordan, based on seven theoretical models and a comprehensive survey. This paper employs a quantitative methodology based on a statistical survey of ESCOs in Jordan during 2018. The survey, which covers 120 firms, explores four sets of measures: technical, functional, corporate image and economic. The empirical results illustrate that energy efficiency improvement contributes to saving of substantial energy hence minimizing the emission of greenhouse gas. The results of the survey showed that 60% of respondents are convinced of the provided services. The highest rate (75%) was for the completion of the transaction which is met the deadlines, the rate for the continuous service amelioration provided by the company is 71%, and 63% for those who believed that public safety is taking into consideration by the company. The results also showed that 60% of the respondent are convinced with an employee’s performance, which is appeared from their answers by strongly agree or agree. The highest rate of 70% of respondent believes that the staff are well- behaved and nice to deal with. For government policies, reducing energy use and promoting investment in the technologies of energy efficiency, as viewed by ESCOs, are key factors in improving energy efficiency and reducing barriers. Keywords: Energy efficiency; Energy resources; Energy supply; Jordan JEL Classifications: Q40, Q43, Q48 DOI: https://doi.org/10.32479/ijeep.10811